High Refractive Index Electromagnetic Devices in Printed Technology Based on Glide-Symmetric Periodic Structures - Philip Arnberg; Oscar Barreira Petersson; Oskar Zetterstrom; Fatemeh Ghasemifard; Oscar Quevedo-Teruel (Applied Sciences, 2020)
We demonstrate the beneficial effects of introducing glide symmetry in a two-dimensional periodic structure. Specifically, we investigate dielectric parallel plate waveguides periodically loaded with Jerusalem cross slots in three configurations: conventional, mirror- and glide-symmetric. Out of these three configurations, it is demonstrated that the glide-symmetric structure is the least dispersive and has the most isotropic response. Furthermore, the glide-symmetric structure provides the highest effective refractive index, which enables the realization of a broader range of electromagnetic devices. To illustrate the potential of this glide-symmetric unit cell, a Maxwell fish-eye lens is designed to operate at 5 GHz. The lens is manufactured in printed circuit board technology. Simulations and measurements are in good agreement and a measured peak transmission coefficient of −0.5 dB is achieved.